"Measurement" of Tinnitus. Issue 8 (September 2016) - Henry, James A.
Abstract : Chronic tinnitus is the persistent sensation of hearing a sound that exists only inside the head. The prevalence of tinnitus in adults in the United States is estimated at 10 to 15%. For about 20% of these individuals the tinnitus is significantly bothersome. Although myriad therapies for tinnitus are offered (often at significant cost), most are not evidence based. Difficulty in the assessment and further development of interventions for tinnitus stems from the limitations of techniques used to evaluate these interventions. Questionnaires are widely available to "measure" (tinnitus can only be indirectly measured) functional effects of tinnitus, such as difficulty sleeping and concentrating, and negative emotions such as anxiety, depression, and annoyance. Questionnaires have recently been documented for sensitivity to change in response to intervention (i.e., "responsiveness"). All of these questionnaires function well to assess the overall impact of tinnitus. The limitations mentioned pertain primarily to measures of tinnitus perception, which typically include the psychoacoustic measures of tinnitus loudness and pitch matches, tinnitus spectral content, minimum masking levels, and residual inhibition. These measures, which are obtained routinely in many clinics and as part of research studies, have not been validated for being diagnostic, prognostic, discriminative, or responsive. In order for these measures to become clinically meaningful, normative standards are needed, both for baseline measures and for repeated measures of tinnitus perception. Evidence-based intervention for tinnitus requires accurately measuring both the perception of, and reactions to, tinnitus.